India Development Report 2012-13
India has done well on many indicators of progress inthepost-reform period. However, a lot remains to be done astheeconomy is confronted with macroeconomic challenges such ashighinflation, high current account deficit, depreciation of therupee,high fiscal deficit, and decline in exports. The IndiaDevelopmentReport 2012-13 assesses many such contemporary problemskeeping inview the objectives of the Twelfth Five Year Plan, andexamines thepost-reform performance and policies that are needed inthe nextdecade to achieve various economic, social, andenvironmental goalsof the nation.